IDENTIFYING THE ISSUES FACED BY STUDENTS: A STRATEGIC STEP IN IMPLEMENTING COUNSELING AT PESANTREN - Wirda Hanim; Sudharno Dwi Yuwono; Nizar Wildan Aulia (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2024)
The development of counseling systems in Pesantren or Islamic boarding schools requires a strong foundation of data. This research aims to identify the issues faced by students as a crucial foundation. A survey method was used with the Problem Checklist (DCM) instrument distributed to 49 students at one of the Islamic boarding schools  in Yogyakarta. The results of the study indicate that students face various issues, including health, economic, family, and school environment-related problems. Data analysis emphasizes the importance of a deep understanding of students' issues to design effective interventions. The implementation of counseling services in boarding schools is highly significant in supporting the holistic development of students. Subsequent steps include data scoring, result analysis, and presentation to design counseling programs that meet students' needs. It is hoped that these efforts will enhance students' well-being and academic achievement, strengthening the role of boarding schools as institutions caring for the personal and social development of their students.   Keywords: Pesantren Counseling, Problem Checklist